Role of AI in the Banking Sector: A Study with Reference to Pre and Post Implementation of AI - Paul, Sushmita; Awungshi, Yarso (Nepalese Journal of Management Science and Research, 2026)
Banking sector has undergone a significant transformation with the integration of Artificial Intelligence (AI), shifting from a manual branch-based system to a highly digitalized data-driven system. AI has enabled banks to take faster decision making, cost effectiveness, personalized services and efficient risk management thereby making AI a technologically advanced system for better performance of banks. The objective is to study the Pre and Post implementation of AI in the banking sector and also to analyze the impact of AI on financial performance and on decision-making for banks. The study has been undertaken by selecting public and private sector banks that are adopting AI services in banks, namely, SBI, PNB, ICICI, HDFC, and AXIS. Both primary and secondary sources of data have been considered for the study. For primary data, 76 bank employees were selected for the study. Data were analyzed through SPSS Statistics 26 software. The study shows that there is an improvement in the financial performance and a significant improvement in liquidity, capital adequacy ratios after the application of AI in banks. The scope of the study was limited to Guwahati and Silchar region which consists of only 5 public and private banks. The study will help the banking professional and regulatory bodies to take strategic decision-making and also to maximise higher profitability for the growth of the bank. Overall, the performance of banks has significantly shown positive responses after utilizing and adopting AI-based services, ultimately helped banks to make proper and prompt decisions.